2016
DOI: 10.1080/08039488.2016.1247195
|View full text |Cite
|
Sign up to set email alerts
|

Employment outcome and predictors of competitive employment at 2-year follow-up of a vocational rehabilitation programme for individuals with schizophrenia in a high-income welfare society

Abstract: The results add to existing evidence that competitive employment is attainable for individuals with schizophrenia. High global functioning and self-esteem were strongly associated with competitive employment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
0
31
0
4
Order By: Relevance
“…There are two defined types of burden: objective burden, which refers to the observable costs to the family that results from the disease; and, subjective burden, which includes the individual’s perception of the situation as burdensome [6]. Specifically, the burden of caring for people with mental illness include disruption of everyday life routine, stigma and blame, dissatisfaction with family and relatives, financial problems, physical burden, troubles with adherence of the patients to treatment and problems with health services and governmental support [7]. It was not until the mid-1950s onwards that the experience of burden of informal family caregivers of family members with mental illness drew researchers’ attention’ [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are two defined types of burden: objective burden, which refers to the observable costs to the family that results from the disease; and, subjective burden, which includes the individual’s perception of the situation as burdensome [6]. Specifically, the burden of caring for people with mental illness include disruption of everyday life routine, stigma and blame, dissatisfaction with family and relatives, financial problems, physical burden, troubles with adherence of the patients to treatment and problems with health services and governmental support [7]. It was not until the mid-1950s onwards that the experience of burden of informal family caregivers of family members with mental illness drew researchers’ attention’ [8].…”
Section: Introductionmentioning
confidence: 99%
“…Seccomandi et al. ( 23 ) recently pointed out that the improvement in self-esteem might be a moderator of the response of CR with a link between higher self-esteem at baseline and better competitive employment as well as lower unemployment ( 55 ). However, in another study self-esteem had no influence on cognitive gains ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of these benefits also come from literature: Farreny et al (54) showed an association between improvement in executive functioning after CR and reduction of thought disorders. Seccomandi et al (23) recently pointed out that the improvement in self-esteem might be a moderator of the response of CR with a link between higher self-esteem at baseline and better competitive employment as well as lower unemployment (55). However, in another study self-esteem had no influence on cognitive gains (16).…”
Section: Class 3 (29%)mentioning
confidence: 98%
“…Through a randomization process, three counties offered each of the treatments. Employment specialists who had undertaken 40 hours of training carried out the respective cognitive interventions twice a week over a six-month period (Evensen et al, 2017;Lystad et al, 2016).…”
Section: The Job Management Program (Jump)mentioning
confidence: 99%